Metal ferrites nanoparticles for catalytic and photocatalytic ozonation in wastewater treatment: A review - Pang, Chuan Kian; Collin G. Joseph; Farm, Yan Yan; Jualang Azlan Gansau; Teo, Siow Hwa; Yap, Taufiq Yun Hin; Liew, Rock Keey (Springer Nature, 2023)
The discharge of various pollutant-rich wastewater in large volumes without adequate treatment seriously endangers the environment. Catalytic and photocatalytic ozonation are the alternative methods to make the treated wastewater reusable. Here, we review the recent advances in metal ferrite nanoparticle catalysts, including the various preparation methods, characterization techniques, catalytic mechanisms, and modification strategies. We discuss the current application of metal ferrites as ozone catalysts and the synergistic effect of catalytic and photocatalytic ozonation. The average pollutant removal efficiencies are 20–40% for non-catalytic ozonation, 80–98% for catalytic ozonation and 60–80% for photocatalytic ozonation using metal ferrite.